2022
DOI: 10.1016/j.breast.2022.02.007
|View full text |Cite
|
Sign up to set email alerts
|

On top of that all, now Covid-19, too. A scoping review of specificities and correlates of fear of cancer recurrence in breast cancer patients during COVID-19

Abstract: Fear of cancer recurrence (FCR) is a normal response in cancer survivors and one of the most prevalent reactions reported by up to 87% of them. However, elevated levels of FCR impair well-being, quality of life and professional functioning, and lead to anxiety, depression or PTSD. COVID-19 pandemic can exacerbate FCR symptoms, given the restricting access to follow-up investigations and treatment, the isolation restrictions imposed and the possibility of the medical system becoming overworked. This scoping rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
1
17
1
1
Order By: Relevance
“…As expected, socio-demographic, physical, and psychological factors were associated with FoP in the COVID-19 pandemic according to the most recent review of clinical research. 38 Furthermore, those with a higher level of FoP were more frequently observed during the COVID-19 period than pre-COVID-19. Specifically, cancer patients are even more vulnerable to distress during the pandemic, thus requiring more delicate psycho-oncological care.…”
Section: Discussionmentioning
confidence: 93%
“…As expected, socio-demographic, physical, and psychological factors were associated with FoP in the COVID-19 pandemic according to the most recent review of clinical research. 38 Furthermore, those with a higher level of FoP were more frequently observed during the COVID-19 period than pre-COVID-19. Specifically, cancer patients are even more vulnerable to distress during the pandemic, thus requiring more delicate psycho-oncological care.…”
Section: Discussionmentioning
confidence: 93%
“…57 It has been indicated that the COVID‐19 pandemic can exacerbate the fear of disease progression or recurrence in patients with cancer due to access restrictions on follow‐up and treatment, imposed isolation restrictions, and the possibility that the healthcare systems becomes overworked. 58 The vast majority of patients concern about the impact of delays on treatment and long‐term health. According to recent studies, the fact that most patients reported high fear of recurrence was due to concerns about lack of access to medical services, which were completely limited during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been indicated that the COVID-19 pandemic can exacerbate the fear of disease progression or recurrence in patients with cancer due to access restrictions on follow-up and treatment, imposed isolation restrictions, and the possibility that the healthcare systems becomes overworked. 58 The vast majority of patients concern about the impact of delays on treatment and long-term 59 The level of distress in cancer patients has also increased due to treatment delays. 60 Moreover, changes in treatment have led to concern and fear of disease recurrence in cancer patients, as well as increased levels of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Patients with breast cancer experienced increased health-related concerns related to recurrence due to the pandemic impact, which affected the access to medicine, the communication with health care providers and treatment plans. 15 Women tend to experience a higher degree of mental health issues, eg anxiety, during the COVID-19 pandemic. 16 Worries are defined as anticipations of possible but yet uncertain negative future events, as opposed to anxiety, which is often accompanied by somatic and behavioral aspects: thus, worries are considered as a component of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…17 During the pandemic, vulnerable groups, such as patients with cancer or those at higher risk of cancer, faced a double-trigger: the threat of malignancy, as well as the possibility of acquiring COVID-19 infection. 11,14,15,19,20 To date, several predictors of healthrelated worries have been identified, including younger age or physical impairment in cancer patients, as well as the level of control of the COVID-19 pandemic. 11,19 Resilience allows people to recover or bounce back from adversity or stressful events in their lives.…”
Section: Introductionmentioning
confidence: 99%